Guano and Rice-Hull Ash Application for Flowering Induction on Orange Jessamine (Murraya paniculata (L.) Jack) - Eliazar, Tabitha Trianda; Aziz, Sandra A. (Department of Agronomy and Horticulture, IPB University, 2015)
Orange jessamine (Murraya paniculata (L.) Jack) has high economical values due to its medicinal properties. Orange jessamine leaves contain flavonoid, mexotionin and coumarin. Orange jessamine flowers contain scopoletin that can lower blood pressure and can be used as an anti-inflammatory agent and as anti-allergic. Orange jessamine is often used as an ornamental plant because it has beautiful flowers similar to jasmine, has nice scent, and red color fruits. The aim of this research is to study the effects of guano and rice-hull ash application on flowering induction of orange jessamine. The research was conducted at an organic experimental farm, Bogor Agricultural University, Darmaga (6°30' – 6°45' S, 106°30'-106°45' E) from December 2014 to June 2015 using randomized complete block design. The experiment used four treatments, i.e. guano at 0.4 kg per plant, combination of guano (0.4 kg per plant) and rice-hull ash (3.0 kg per plant), rice-hull ash 3.0 kg per plant and without fertilisation as control. The results showed that the application of rice-hull ash increased plant height and leaf number. Guano application significantly increased the intensity of leaf color in mature orange jessamine leaves. Rice-hull ash application increased flower number at 12 and 20 weeks after application.Keywords: chlorophyll, flower number, flower weight, NPK value, organic farming